POLA MAKAN DAN STATUS GIZI REMAJA DI DESA ADAT BUNGAYA KABUPATEN KARANGASEM - Ni Kadek Dwi Laras Genarsih; I Komang Agusjaya Mataram; I Ketut Kencana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Nutrition is one of the most important factors and major development determinants of teenager growth, as in adolescence, the hormonal changes that cause the rapid growth of other phases in life except the first year of life. This research aimed to investigate the dietary habit and teenager's nutritional status at Bungaya Traditional Village, Karangasem Regency. This research method used cross sectional method. The samples of research were 41 teenager with an age range of 13-18 years old who are living at Dusun Beji in Bungaya Village, Karangasem Regency. Dietary habbit was umeasured by the Food Recall 1x24 hours and nutritional status of BMI. Data analysis describe according to the purpose. The results showed as much of 41 total samples of 34 samples (82.9%) had dietary habit in the good diet pattern categories with a tendency to have a normal nutritional status were 20 people (58.8%) of the total sample with a good diet habbt. Obeses was 7 samples (20.6%), overweight was 6 samples (17.6%) and thinness was 1 sample (2.9%). While the sample with enough dietary habbit as many as 7 people consisted of 5 samples (71.4%) with normlal nutritional status and 2 samples (28.6% ) of the total sampelts with enough dietary habbit included in thinness. Food frequency, type and amount of food will affect food intake which will have an impact on nutritional status. Then there needs to be improvements in food consumption both in quantity and quality and variety of food menus. Meal frequency, type and amount of food would affect food intake that have an impact on nutritional status. So it needed for improvements in dietary habit both in quantity and quality and variety of the food menu.Keywords             : Dietary habbit, Nutritional status, Teenagers